2020
DOI: 10.1002/adma.201907006
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Assembly of 2D Materials for Energy and Environmental Applications

Abstract: Rational design of 2D materials is crucial for the realization of their profound implications in energy and environmental fields. The past decade has witnessed significant developments in 2D material research, yet a number of critical challenges remain for real‐world applications. Nanoscale assembly, precise control over the orientational and positional ordering, and complex interfaces among 2D layers are essential for the continued progress of 2D materials, especially for energy storage and conversion and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(66 citation statements)
references
References 251 publications
(325 reference statements)
0
63
0
Order By: Relevance
“…52,128,129 2D materials have attracted widespread attention for electrocatalytic applications because of their high specic areas, high surface-to-volume ratios, and fast electrontransfer rates. 61,130,131 The atomic utilization efficiency of nanosheets will increase as the thickness decreases. Theoretically, when the thickness of a nanosheet reaches only two atomic layers, the atom utilization efficiency can reach 100%.…”
Section: Two-dimensional (2d) Structuresmentioning
confidence: 99%
“…52,128,129 2D materials have attracted widespread attention for electrocatalytic applications because of their high specic areas, high surface-to-volume ratios, and fast electrontransfer rates. 61,130,131 The atomic utilization efficiency of nanosheets will increase as the thickness decreases. Theoretically, when the thickness of a nanosheet reaches only two atomic layers, the atom utilization efficiency can reach 100%.…”
Section: Two-dimensional (2d) Structuresmentioning
confidence: 99%
“…Because 2D TMOs and TMCs generally lack structural motifs for specific intermolecular interactions (such as hydrogen bonding sites or amphiphilic structures for hydrophobic interaction) that are present in biomolecules or polymeric molecules built from molecular self‐assembly, spontaneous oriented assembly is largely precluded. [ 100 ] In studying the hydrothermal growth of pure SnO 2 NPs in water without any surfactant, Zhuang et al found that the pure SnO 2 NPs formed microsphere aggregates in a highly random manner. [ 101 ] Regrettably, the aggregate cannot form 2D materials but undergoes an ultrafast growth from ≈4 nm SnO 2 nanocrystals to ≈350 nm bulk crystals.…”
Section: Synthesis and Growth Of Freestanding 2d Tmos And Tmcsmentioning
confidence: 99%
“…Further study on ultrathin nanosheet (Figure 5A) reveals both ORR and OER performances can be enhanced by high metal content (Co loading is 15.3%). It is broadly admitted that 2D materials favor the high exposure of abundant catalytic active sites, and the relative thin thickness presents favorable mass and electron transport pathways by reducing the electrolyte transport distance 113‐117 . Furthermore, the high atomically metal content induces the formation of more M‐N‐C actives sites within the N‐doped 2D carbon matrix.…”
Section: Tm/carbon Hybrids For Oxygen Electrocatalystsmentioning
confidence: 99%